The impact of the unofficial relationship on the university student’s studies, time and mental health - Chitrali, Saith Usama J. (Pakistan Review of Social Sciences (PRSS), 2020)
The unofficial relationships are described as “The commitment between the two people i.e. male and female supporting each other physically and emotionally without fulfilling any religious procedure or legal process defined under law and owning the social define responsibilities”. It has been considered that nowadays the institutions are changing into the dating hubs and students are getting involve with each other which is causing effect on their study, time, financial condition and mental health. The methodology which is design to conduct the research is in two phases; in the first phase of the study we have tried to assess the student’s condition through collecting the questionnaire from the different institutes in the territory of Islamabad which is chosen due to the diversification. In the second phase we conducted the interviews with the instructors and educationist those have the direct linkages with the students and observing them on a regular basis. The assumptions of the research which were made depicts accurate to the assumption design upon the literature review. The students are going mainly through the issues of the mental health and time schedule disturbance. While students are facing the challenges regards to the studies and financial condition which are creating the challenges for their professional life. This study is going to gives exposure base understanding of the impact been faced by the students in the academic institutes and their disturbing their personal and professional life.